Prosperity Gospel and the Spirit of Capitalism: The Nigerian Story - Umoh, Dominic (African Journal of Scientific Research, 2013)
There are many pastors who may not have properly understood the demands of the pastoral ministry but just chanced upon the latter while searching for a means of livelihood. There are others who may have arrived at the apostolate with preconceived ideas: A buoyant and flamboyant lifestyle, material comfort including wealth, power and sex. Now in an age of crass materialism, when many would do anything in order to achieve maximum wealth, success, comfort and popularity, when the human conscience has been stifled by inordinate desires and the temptation for material relevance, many men and women of God have completely lost their bearing concerning the essence of the good news of Christ. They have thrown overboard the demands of the Gospel message regarding moral rectitude, Christ-like modesty and the yearning for the spiritual all in pursuit of material gains at all cost. Using a critical philosophical analysis, the author argues against the misguided tenets of materialistic salvation as woefully lacking in appropriate models for authentic Christian life.